CAROTENOID-ENRICHED DIET FOR PREMATURATION STAGE OF POND- REARED TIGER SHRIMP, Penaeus monodon: Part II. EFFECT ON GONADAL MATURATION AND BIOCHEMICAL PROFILES OF OOCYTES, SPERMATOPHORES AND HEPATOPANCREAS - Asda Laining; Ike Trismawanti; Muhammad Chaidir Undu; Andi Sahrijanna; Andi Indra Jaya Asaad (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
Two-phase feeding trials were conducted to evaluate the effect of the carotenoid mixture on gonadal development and biochemical properties of several tissues of tiger shrimp. The treatments were diet enriched with (PC) and without carotenoid mixture (PO). Shrimp with an initial body weight of 31.7±1.3 g were allocated among four of 1,000 m2 concrete ponds with a density of 1 shrimp/m2 and fed tested diets for five months. Selected shrimps from the pond with a minimum weight of 80 g for females and 60 g for males were stocked into four 10-m3 concrete tanks at 15 pairs per tank. Natural mating rate and ovary development were not stimulated by the carotenoid supplement. However, it significantly improved (P<0.05) both ovary maturation and spermatophore formation of tiger shrimp from 76.7±1.4 to 86.7±0.0% and from 69.9 ±4.5 to 82.3±4.0%, respectively. Total carotenoid content in meat, oocyte and hepatopancreas of female tiger shrimp significantly (P<0.05) increased by supplementing carotenoid compared to the control diet. The total amino acid content in the spermatophore of shrimp fed the PC diet was significantly higher (73.82%) than in the PO diet (66.09%). The present study revealed the important effect of carotenoid feed during the pre-maturation stage on the reproductive performances of pond-reared tiger shrimp.